Aktivitas Antidiabetes Ekstrak Etanol Daun Singkong (Manihot utilissima Pohl.) pada Tikus yang Diinduksi Insulin Kerja Panjang: Antidiabetic Activity of Ethanolic Extract of Cassava (Manihot utilissima Pohl.) Leaves in Long Acting Insulin-Induced Rats - Aljufri, Achmad Quraisy; Damayanti, Kiki; Fasikha, Fasikha (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
The antidiabetic activity of cassava leaves in type 1 DM mice has been studied previously. Secondary metabolites that may play a role in DM therapy are flavonoids. It is necessary to explore the activity of cassava leaves as a therapy for type 2 diabetes. This study aims to confirm the presence of flavonoids in the ethanol extract of cassava leaves (EEDS), followed by testing the antidiabetic activity of the extract in type 2 DM rats induced by long-acting insulin. The maceration method is a method for making EEDS. The presence of flavonoids in EEDS is known through reactions with Pb acetate. Rats as a test animal model were made to experience type 2 DM by being induced by insulin glargine 1.80 IU/kgBW subcutaneously, once a day, for 14 days. A total of 40 rats with type 2 diabetes were divided into 5 groups. Group I was the negative control group which was given 0.5% CMC-Na solution 12.5 mL/kgBW. Group II was the positive control group which was given metformin HCl at a dose of 45 mg/kgBW, 2 times a day. EEDS at a dose of 250; 500; and 750 mg/kgBW was given to rats in group III, IV, and V consecutively. The EEDS was given to rats orally for 14 days. The day after the last EEDS administration, 2-hour postprandial blood glucose levels were measured. EEDS contains flavonoids and has antidiabetic activity. Keywords: antidiabetics, cassava leaves, long acting insulin, Manihot utilissima Pohl. Abstrak Aktivitas daun singkong sebagai antidiabetes pada tikus DM tipe 1 telah diteliti sebelumnya. Metabolit sekunder yang kemungkinan berperan dalam terapi DM adalah flavonoid. Perlu dilakukan eksplorasi aktivitas daun singkong sebagai terapi DM tipe 2. Penelitian ini bertujuan untuk mengonfirmasi keberadaan flavonoid dalam ekstrak etanol daun singkong (EEDS), dilanjutkan pengujian aktivitas antidiabetes ekstrak pada tikus DM tipe 2 yang diinduksi insulin kerja panjang. Metode maserasi merupakan metode pembuatan EEDS. Keberadaan flavonoid dalam EEDS diketahui melalui reaksi dengan Pb asetat. Tikus sebagai model hewan uji dibuat mengalami DM tipe 2 dengan diinduksi insulin glargine 1,80 IU/kgBB secara subkutan, 1 kali sehari, selama 14 hari. Tikus DM tipe 2 sebanyak 40 ekor dibagi menjadi 5 kelompok. Kelompok I merupakan kelompok kontrol negatif yang diberi larutan CMC-Na 0,5% 12,5 mL/kgBB. Kelompok II merupakan kelompok kontrol positif yang diberi metformin HCl dosis 45 mg/kgBB, 2 kali sehari. EEDS dosis 250; 500; dan 750 mg/kgBB diberikan pada tikus kelompok III, IV, dan V. Senyawa uji diberikan pada tikus secara per oral selama 14 hari. Sehari setelah senyawa uji terakhir, kadar glukosa darah 2 jam postprandial diukur. EEDS mengandung flavonoid dan punya aktivitas sebagai antidiabetes. Kata Kunci: antidiabetes, daun singkong, insulin kerja panjang, Manihot utilissima Pohl.